Self-Efficacy as a Positive Youth Development Construct: A Conceptual Review - Sandra K. M. Tsang; Eadaoin K. P. Hui; Bella C. M. Law (The Scientific World Journal)
Self-efficacy denotes people's beliefs about their ability to perform in different situations. It functions as a multilevel and multifaceted set of beliefs that influence how people feel, think, motivate themselves, and behave during various tasks. Self-efficacy beliefs are informed by enactive attainment, vicarious experience, imaginal experiences, and social persuasion as well as physical and emotional states. These beliefs are mediated by cognitive, motivational, affective, and selection processes to generate actual performance. Self-efficacy development is closely intertwined with a person's experiences, competencies, and developmental tasks in different domains at different stages in life. This paper reviews the literature to outline the definition and theoretical conceptualizations of the construct originally devised by Bandura that have flourished since the 1990s. Drawing from the studies of the construct to assess self-efficacy, and to inform positive youth development, the paper will present the determinants of the development of self-efficacy beliefs and identify the connection between self-efficacy and adolescent developmental outcomes. The paper will conclude with strategies to enhance youth self-efficacy and proposals for future research directions.